High quality metal-quantum dot-metal structure fabricated with a highly compatible self-aligned process*Project supported by the National Basic Research Program of China (No. 2011CB922103), and the National Natural Science Foundation of China (Nos. 61376420, 61404126, A040203). (December 2015) - Fu 付, Yingchun 英春; Wang 王, Xiaofeng 晓峰; Ma 马, Liuhong 刘红; Zhou 周, Yaling 亚玲; Yang 杨, Xiang 香; Wang 王, Xiaodong 晓东; Yang 杨, Fuhua 富华
Abstract: A self-aligned process to fabricate a "metal-quantum dot-metal" structure is presented, based on an "electron beam lithography, thin film deposition and dry etching process". The sacrificial layers used can improve the lift-off process, and novel lithography layouts design can improve the mechanical strength of the fabricated nanostructures. The superiority of the self-aligned process includes low request for overlay accuracy, high compatibility with a variety of materials, and applicable to similar structure devices fabrication. Finally, a phase change memory with fully confined phase-change material node, with the length × width × height of 255 × 45 × 30 nm 3 was demonstrated.